Picornaviridae and Caliciviridae diversity in Madagascar fruit bats is driven by cross-continental genetic exchange - Kettenburg, Gwenddolen; Ranaivoson, Hafaliana C; Andrianianina, Angelo; Andry, Santino; Henry, Amy R; Davis, Rachel L; Laboune, Farida; Longtine, Elizabeth R; Godbole, Sucheta; Horigan, Sophia; Ruhs, Emily Cornelius; Raharinosy, Vololoniaina; et al. (bioRxiv, 2025)
Bats are reservoir hosts for numerous well-known zoonotic viruses, but their broader virus-hosting capacities remain understudied. are an order of enteric viruses known to cause disease across a wide range of mammalian hosts, including Hepatitis A in humans and foot-and-mouth disease in ungulates. Host-switching and recombination drive the diversification of worldwide. Divergent and (families within the ) have been described in bats across mainland Africa, but surveillance for these viruses has been rare in the Southwest Indian Ocean Islands. Bats live in close proximity to and are consumed widely as a food source by humans in Madagascar, providing opportunities for zoonotic transmission. Prior work in Madagascar has described numerous evolutionarily divergent bat viruses, some with zoonotic potential. Using metagenomic Next Generation Sequencing of urine and fecal samples obtained from three species of endemic Malagasy fruit bats ( , , and ), we recovered 13 full-length and 37 partial-length genomic sequences within the order (36 and 14 sequences), which we identify and describe here. We find evidence that genetic exchange between mainland African bat and Madagascar bat likely shaped the diversification patterns of these novel sequences through recombination events between closely related ; thus far, high host fidelity appears to have limited these viruses from spilling over into other species.